2020
DOI: 10.3390/children7030021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Need-Supportive Motor Skill Intervention on Children’s Motor Skill Competence and Physical Activity

Abstract: A need-supportive environment can provide various motivational benefits to impact children’s psychomotor developmental levels. However, very little is known about the effects of need-supportive motor skill intervention on children’s motor skill competence and physical activity by gender. Guided by self-determination theory (SDT), this study aimed to (a) investigate the effect of a need-supportive fundamental movement skill (FMS) program on children’s FMS competence and moderate-to-vigorous physical activity (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 57 publications
(67 reference statements)
2
37
0
7
Order By: Relevance
“…Thus, we must not forget that the development of motor competence in boys and girls is one of the objectives of PE [22,23], and the development of motor competence is considered a critical element within a quality PE class since it provides an inclusive, qualified and meaningful opportunity for all children [24]. For these reasons, motor competence has become one of the most important contents to work on in compulsory schooling [25,26], as included in the study plans designed by educational administrations [23], because the development of each child is of special importance to them since motor skills are essential for their integral development [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we must not forget that the development of motor competence in boys and girls is one of the objectives of PE [22,23], and the development of motor competence is considered a critical element within a quality PE class since it provides an inclusive, qualified and meaningful opportunity for all children [24]. For these reasons, motor competence has become one of the most important contents to work on in compulsory schooling [25,26], as included in the study plans designed by educational administrations [23], because the development of each child is of special importance to them since motor skills are essential for their integral development [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Afterschool programs can be efficacious for implementing jump rope exercise since they allow students to participate in a variety of movements and physical activities [ 27 , 28 ]. Previous evidence has shown that an afterschool PA program brings multiple health benefits, including increased PA behaviors [ 29 ], working memory [ 30 ], motor skills competence [ 31 ], reduced body fat [ 32 ], and increased academic motivation and effort [ 33 ]. It was also noted that adolescents’ MVPA was strongly associated with supervised PA and accessibility to sports equipment and facilities during afterschool programs [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of participating in sufficient physical activity (PA) in childhood and adolescence and the benefits of PA on physical health, mental health, academic performance, and social well-being have been well proven [ 1 , 2 , 3 , 4 , 5 ]. However, the decrease in participation in PA in adolescence is recognized as a global problem, which is additionally important since a decrease in PA may extend into adult life [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%